Efficient modeling of liquid phase photoemission spectra and reorganization energies: Difficult case of multiply charged anions - Rubešová, Martina; Jurásková, Veronika; Slavíček, Petr (Journal of computational chemistry, 2017)
An efficient approach for quantitative modeling of liquid phase photoelectron spectra, reorganization energies, and redox potentials with DFT-based molecular dynamics simulations is presented. The method is based on a large scale cluster-continuum approach combined with the so-called reflection principle (RP). Finite size clusters of solute molecules with solvating water molecules are at first generated using either classical molecular dynamics or molecular dynamics with a quantum thermostat which accounts for nuclear quantum effects. In the next step, the electron binding energies are calculated. Finite-size corrections for (i) positions of electron binding energies and (ii) width of the spectrum are evaluated via a dielectric continuum approach. The performance of such a reflection principle with additional broadening approach (RP-AB) for oxidation of multiply charged iron anions, [Fe(CN)6 ]4- and [Fe(CN)6 ]3- is demonstrated. The role of nuclear quantum effects is discussed as well as the relation between spectroscopic data and electrochemical quantities. Results are compared with recent liquid photoemission experiments, explaining the obstacles for applying liquid phase photoemission spectroscopy as a direct method for obtaining absolute redox potentials and suggesting a way to overcome them. © 2017 Wiley Periodicals, Inc.
Keywords: reorganization energy; ab initio path integral molecular dynamics; photoemission spectroscopy; ab initio electrochemistry; absolute redox potentials